2016
DOI: 10.1155/2016/8794696
|View full text |Cite
|
Sign up to set email alerts
|

Place of Colistin-Rifampicin Association in the Treatment of Multidrug-ResistantAcinetobacter BaumanniiMeningitis: A Case Study

Abstract: Treatment of Acinetobacter baumannii meningitis is an important challenge due to the accumulation of resistance of this bacteria and low meningeal diffusion of several antimicrobial requiring use of an antimicrobial effective combination to eradicate these species. We report a case of Acinetobacter baumannii multidrug-resistant nosocomial meningitis which was successfully treated with intravenous and intrathecal colistin associated with rifampicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…A systematic review of the evidence regarding clinical efficacy and safety of IVT or ITH colistin or polymyxin B was conducted . A total of 234 cases of gram‐negative health care–associated ventriculitis or meningitis treated with IVT or ITH colistin or polymyxin B were reported.…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 97%
See 1 more Smart Citation
“…A systematic review of the evidence regarding clinical efficacy and safety of IVT or ITH colistin or polymyxin B was conducted . A total of 234 cases of gram‐negative health care–associated ventriculitis or meningitis treated with IVT or ITH colistin or polymyxin B were reported.…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 97%
“…153 A systematic review of the evidence regarding clinical efficacy and safety of IVT or ITH colistin or polymyxin B was conducted. [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176] A total of 234 cases of gram-negative health care-associated ventriculitis or meningitis treated with IVT or ITH colistin or polymyxin B were reported. Intraventricular or ITH colistin was administered in 87% of cases and polymyxin B in the remaining 13%.…”
Section: Should Intraventricular or Intrathecal Administration Ofmentioning
confidence: 99%
“…Был проведен систематический обзор доказательных данных в отношении клинической эффективности и безопасности ИВТ или ИТК введения колистина [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]. В общей сложности было включено 234 случая нозокомиального грамотрицательного вентрикулита или менингита, в отношении которых применялось ИВТ или ИТК введение колистина или полимиксина В. Интравентрикулярный или ИТК колистин применялся в 87% случаев, в то время как полимиксин В -в оставшихся 13%.…”
Section: антимикробные препаратыunclassified
“…Results of comprehensive literature search for case reports with colistin as treatment for patients with intracranial infections published expanding the recent reviews. 3,[10][11][12] 170.000 IU (mean ± 400 IU) 9 MIU -Hospital mortality: 3/23 IVT, 8/11 IV De Bonis et al 3 18 (9 IV, 9 IVT) 10-20 mg (0.25-0.5 MIU) -12/18 (9/9 IVT, 3/9 IV) 4/9 IVT, 7/9 IV Shofty et al 5 95, of which 50 were analyzed Median dose 0.05 MIU (range, 0.05-0.25 MIU/day) 22 patients were treated --30-day mortality: 2/23 IVT (1/10 Col-IVT) 9/27 IVT Souhail et al 9 1 0.125 MIU/day 12 MIU -0/1 IV: intraventricular colistin therapy only; IVT: intraventricular + intravenous combination therapy; MIU: million international units.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Recommendations were given by the Infectious Disease Society of America in 2004 2 including intraventricular antibiotic therapy and this has also been discussed in a comment from the European medicines agency 2014. For infections due to MDR Gram-negative pathogens, the intraventricular administration of colistin was successfully used in a wide range of case studies, 3 9 exemplarily reported by Karaiskos et al, 8 by Souhail et al in combination with rifampicin, and by Dalgic et al 7 in a girl of 2 months. Evidence for colistin therapy is also summarized in reviews 3 , 10 – 12 reporting an overall clinical response rate of about 90%.…”
Section: Introductionmentioning
confidence: 99%